Nursing Care For Stroke Patients Given A-I-U-E-O Speech Therapy In The Flamboyan Room Of Banjar City Hospital - Cahyati, Yanti; Anggraeni, Putri; Rahman, Arip (Jurnal Kesehatan Mahardika, 2023)
Background: Stroke is a condition in which clinical symptoms appear in the form of neurological deficits, both focal and global, that last long enough, usually more than 24 hours. One of the impacts that occur is in the form of verbal communication disorders that have a physical and psychological impact on the sufferer. Purpose: Explain the nursing care process for stroke patients who are given A,I,U,E,O speech therapy directly and comprehensively. Methodology: Qualitative the form of a case study approach, with speech therapy intervention techniques A,I,U,E,O in the form of imitation. Results: Two respondent experienced verbal communication disorders, so that they were given implementation in the form of A,I,U,E,O speech therapy for five days with 2x implementation in 1 day and there was an increase in speech in both study subjects characterized by an increase in LAST (Language Screening Test) scores, improved speaking ability, increased expression or facial suitability, increased eye contact and decreased pelo. Conclusion: A,I,U,E,O speech is effective in stroke patients with verbal communication disorders.